The potential use of mobile phone technology for knowledge sharing among academics in institution of higher learning - Nassuora, Ayman Bassam; Hasan, Shahizan (2010)
The potentials of mobile phone technology are huge and it has opened possibilities and avenues for enhancing knowledge sharing activities among academics in Institutions of Higher Learning (IHLs).However, it was found that there was lack of academic research on the use of mobile phone technologies for knowledge sharing purposes in IHLs. In IHLs, technologies of mobile phones such as cell phones, smart phones, and PDAs provided with interesting features like camera, video, memory, player of MP3, internet approach and finally, presence in a device, by allowing study anywhere, anytime.This paper aimed to understand academics’ general attitudes towards the use of mobile phone technology in IHLs, to explore the academics perceived usefulness to use mobile phone technology in IHLs, to determine academics’ perceived ease of use of mobile phone technology in IHLs, to understand academics behavioral intention to use mobile phone technology in IHLs, to identify how will mobile phone technologies change the work situation of academics, and to identify the possible services that, in their opinion, can improve mobile phone technology and knowledge sharing among academics in IHLs. The overall findings revealed that there were at least four factors could lead to the adoption of mobile phone technology among academics in an Institution of Higher Learning.These factors were; attitudes towards the use of mobile phone technology, perceived usefulness to use mobile phone technology, perceived ease of use of mobile phone technology, and behavioral intention to use mobile phone technology.